Snails & monkey tails : a visual guide to punctuation & symbols - Arndt, Michael (Michael Peter) (Harper Design, an imprint of HarperCollinsPublishers, 2021)
"Snails & Monkey Tails is a show-stopping guide to the punctuation marks and symbols used in the English language. Perfect for bibliophiles, writers, grammarians, graphic designers, typography freaks, logophiles, and anyone with a passion for the written word, this rollicking linguistic ride by award-winning graphic designer Michael Arndt is a beautifully designed volume--with more than 75 uniquely designed eye-catching red, white, and black spreads--that explores both the typographic origins, names, and shapes of punctuation and symbols and covers the proper and diverse usage of each"--